Chromosomal rearrangements and the first indication of an ♀X1 X1 X2 X2 /♂X1 X2 Y sex chromosome system in Rineloricaria fishes (Teleostei: Siluriformes) - Marajó, Leandro; Viana, Patrik Ferreira; Ferreira, Alex Matheus Viana; Py-Daniel, Lúcia Helena Rapp; Cioffi, Marcelo de Bello; Sember, Alexandr; Feldberg, Eliana (Journal of fish biology, 2023)
Rineloricaria is the most diverse genus within the freshwater fish subfamily Loricariinae, and it is widely distributed in the Neotropical region. Despite limited cytogenetic data, records from southern and south-eastern Brazil suggest a high rate of chromosomal rearrangements in this genus, mirrored in remarkable inter- and intraspecific karyotype variability. In the present work, we investigated the karyotype features of Rineloricaria teffeana, an endemic representative from northern Brazil, using both conventional and molecular cytogenetic techniques. We revealed different diploid chromosome numbers (2n) between sexes (33♂/34♀), which suggests the presence of an ♀X1 X1 X2 X2 /♂X1 X2 Y multiple sex chromosome system. The male-limited Y chromosome was the largest and the only biarmed element in the karyotype, implying Y-autosome fusion as the most probable mechanism behind its origination. C-banding revealed low amounts of constitutive heterochromatin, mostly confined to the (peri)centromeric regions of most chromosomes (including the X2 and the Y) but also occupying the distal regions of a few chromosomal pairs. The chromosomal localization of the 18S ribosomal DNA (rDNA) clusters revealed a single site on chromosome pair 4, which was adjacent to the 5S rDNA cluster. Additional 5S rDNA loci were present on the autosome pair 8, X1 chromosome, and in the presumed fusion point on the Y chromosome. The probe for telomeric repeat motif (TTAGGG)n revealed signals of variable intensities at the ends of all chromosomes except for the Y chromosome, where no detectable signals were evidenced. Male-to-female comparative genomic hybridization revealed no sex-specific or sex-biased repetitive DNA accumulations, suggesting a presumably low level of neo-Y chromosome differentiation. We provide evidence that rDNA sites might have played a role in the formation of this putative multiple sex chromosome system and that chromosome fusions originate through different mechanisms among different Rineloricaria species.
Keywords: chromozom Y; Sex Chromosomes; Robertsonian fusion; Male; sex chromosome evolution; pohlavní chromozomy; repetitive DNA; srovnávací genomová hybridizace; Y Chromosome; ribozomální DNA; karyotyp; mužské pohlaví; Catfishes; Amazon basin; Animals; ženské pohlaví; fluorescence in situ hybridization; zvířata; Comparative Genomic Hybridization; DNA, Ribosomal; Female; sumci; Karyotype